Discrepancies in current practice of pathological evaluation of sentinel lymph nodes in breast cancer. Results of a questionnaire based survey by the European Working Group for Breast Screening Pathology. Issue 7 (25th June 2004) - Cserni, G; Amendoeira, I; Apostolikas, N; Bellocq, J P; Bianchi, S; Boecker, W; Borisch, B; Connolly, C E; Decker, T; Dervan, P; Drijkoningen, M; Ellis, I O; et al.
Abstract : Aims: To evaluate aspects of the current practice of sentinel lymph node (SLN) pathology in breast cancer via a questionnaire based survey, to recognise major issues that the European guidelines for mammography screening should address in the next revision. Methods: A questionnaire was circulated by mail or electronically by the authors in their respective countries. Replies from pathology units dealing with SLN specimens were evaluated further. Results: Of the 382 respondents, 240 European pathology units were dealing with SLN specimens. Sixty per cent of these units carried out intraoperative assessment, most commonly consisting of frozen sections. Most units slice larger SLNs into pieces and only 12% assess these slices on a single haematoxylin and eosin (HE) stained slide. Seventy one per cent of the units routinely use immunohistochemistry in all cases negative by HE. The terms micrometastasis, submicrometastasis, and isolated tumour cells (ITCs) are used in 93%, 22%, and 71% of units, respectively, but have a rather heterogeneous interpretation. Molecular SLN staging was reported by only 10 units (4%). Most institutions have their own guidelines for SLN processing, but some countries also have well recognised national guidelines. Conclusions: Pathological examination of SLNs throughout Europe varies considerably and is not standardised. The European guidelines should focus on standardising examination. They should recommend techniques that identify metastases > 2 mm as a minimum standard. Uniform reporting of additional findings may also be important, because micrometastases and ITCs may in the future be shown to have clinical relevance.